Genomic Diversification of Enterococci in Hosts: The Role of the Mobilome - Santagati, Maria; Campanile, Floriana; Stefani, Stefania (Frontiers in Microbiology, 2012)
Enterococci are ubiquitous lactic acid bacteria, possessing a flexible nature that allows them to colonize various environments and hosts but also to be opportunistic pathogens. Many papers have contributed to a better understanding of: i) the taxonomy of this complex group of microorganisms; ii) intra-species variability; iii) the role of different pathogenicity traits; and iv) some markers related to the character of host-specificity, but the reasons of such incredible success of adaptability is still far from being fully explained. Recently, genomic-based studies have improved our understanding of the genome diversity of the most studied species i.e. E. faecalis and E. faecium. From these studies, what is becoming evident is the role of the mobilome in adding new abilities to colonize new hosts and environments, and eventually in driving their evolution: specific clones associated with human infections or specific hosts can exist, but probably the consideration of these populations as strictly clonal groups is only partially correct. The variable presence of mobile-genetic elements may, indeed, be one of the factors involved in the evolution of one specific group in a specific host and/or environment. Certainly more extensive studies using new high throughput technologies are mandatory to fully understand the evolution of predominant clones and species in different hosts and environments.